STABILISASI TANAH LEMPUNG DENGAN BAHAN ADITIF FLY ASH SEBAGAI LAPISAN PONDASI DASAR JALAN (SUBGRADE) - Ibrahim Ibrahim (PILAR, 2014)
Some road construction in Indonesia built on expansive clay soil. Strong support is strongly influenced clay water content, in a dry state has a strong support and high in saturated state will have a strong low carrying capacity. Water content will affect the nature of the flower shrinkage and shear strength parameters of soil. Construction of roads built on clay soil often damaged, eg cracked or bumpy roads would be damaged so that road before reaching the age of the plan. To overcome the problems of the clay where the strong supporting affected by water content, one alternative be repaired by means of stabilization. This study analyzes the behavior of clay in the area of Tanjung Api Spinner - fire, get maximum soil density and optimum moisture content with the addition of fly ash (coal) 2.5%, 5%, 7.5%, 10% and 12.5%, then tested in the form of nature - the nature of the soil, the California Bearing Ratio (CBR) and unconfined compression(compressive streng this free). The results, according to the AASHTO classification including group A-7-6. The addition of fly ash will cause the properties of the soil liquid limit (LL) decreased with plastic limit (PL) decreased so that the plasticity index (PI) decreased, then the percentage of grains resulting in the fine fraction decreases with increasing clay gradation. The addition of fly ash will be working actively on the CBR test. It can be concluded that the fly ash work filling and covering the pores - pore soil thereby increasing soil kekedapan to the addition of water and increase soil strengthatsaturationwithoutchangingthephysicalpropertiesofsoil.